Charting a New Course : Priorities for a Vibrant Economy and Jobs - Policy Choices for Malawi 2019 - World Bank Group (World Bank, Washington, DC, 2019)
The start of a new administration offers a tremendous opportunity for Malawi to build upon recent progress to move beyond a history of low growth and limited poverty reduction. This package of policy notes is addressed to Malawian society and to the beginning of a new administration following the May 2019 elections. It provides the World Bank’s diagnosis of Malawi’s main economic and social development challenges and charts a possible course to address them. The insights offered draw upon a wealth of analysis carried out in the past few years by the World Bank country team, including a comprehensive Systematic Country Diagnostic and a recent Country Economic Memorandum.